1969
DOI: 10.1128/am.17.1.106-110.1969
|View full text |Cite
|
Sign up to set email alerts
|

Procedure for Evaluating the Effects of 2,450- Megahertz Microwaves upon Streptococcus faecalis and Saccharomyces cerevisiae

Abstract: Modifications of a commercial 2,450-megahertz microwave oven were made so that 6 ml of microbial suspension could be exposed to the microwave field for various periods of time. The microorganisms were contained in the central tube of a modified Liebig condenser positioned in the approximate geometric center of the oven cavity. Kerosene at -25 C was circulated through the jacket of the condenser during microwave exposure permitting microwaves to reach the microbial suspension. Flow rates of the kerosene were va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1971
1971
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Welt et al [ 11 ] also found no difference between conventional and microwave deactivation of Clostridium sporogenes at 90°C, 100°C, and 110°C. Lechowich et al [ 12 ], Vela et al [ 13 ], Rosén [ 14 ] also found that the deactivation of several bacteria, including Streptococcus faecalis (later classified as Enterococcus faecalis ) and Saccharomyces cerevisiae , under microwave irradiation resulted from the dielectric heating.…”
Section: Introductionmentioning
confidence: 99%
“…Welt et al [ 11 ] also found no difference between conventional and microwave deactivation of Clostridium sporogenes at 90°C, 100°C, and 110°C. Lechowich et al [ 12 ], Vela et al [ 13 ], Rosén [ 14 ] also found that the deactivation of several bacteria, including Streptococcus faecalis (later classified as Enterococcus faecalis ) and Saccharomyces cerevisiae , under microwave irradiation resulted from the dielectric heating.…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of researches had been published on the effect of such radiation on the growth of different microorganisms which due to either thermal and non-thermal effect. Most of the researchers are with thermal effect in which the exposed cells absorb microwave energy and leading to heating that cause denaturation of cellular enzymes and proteins [3][4][5][6][7][8][9][10]. On the other hand, some of the researchers concluded that the bacterial growth was increased when exposed to low power levels of radiation [11].…”
Section: -Introductionmentioning
confidence: 99%
“…Conversely, some believe that thermal effect of the microwave alone can have a bactericidal and sporicidal effect, especially in liquid systems [17, 18]. Vela and Wu [19] observed that dry or lyophilized microorganisms are not capable of absorbing microwave energy.…”
mentioning
confidence: 99%